2021
DOI: 10.1016/j.jbc.2021.100368
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of carbohydrate binding by the macrophage mannose receptor CD206

Abstract: The human mannose receptor expressed on macrophages and hepatic endothelial cells scavenges released lysosomal enzymes, glycopeptide fragments of collagen, and pathogenic microorganisms and thus reduces damage following tissue injury. The receptor binds mannose, fucose, or N-acetylglucosamine (GlcNAc) residues on these targets. C-type carbohydrate-recognition domain 4 (CRD4) of the receptor contains the site for Ca 2+ -dependent interaction with sugars. To investigate the details of CRD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…As an MMR-targeted theranostic agent, the NIRF-emitting MMR carrier was prepared to specifically deliver lobeglitazone into plaque macrophages and scaled up for the translational application to the plaques in coronary-sized arteries. Previous studies have reported that D-mannose had higher binding affinity towards mannose receptors than other monosugars (i.e., N-acetylglucosamine, glucose, xylose, and galactose) 33 - 37 . In this study, we used mannosamine as a specific ligand to mannose receptors because it has the equatorial hydroxyl groups at both the C3 and C4 positions that are the principal determinants of recognition towards mannose receptors ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 92%
“…As an MMR-targeted theranostic agent, the NIRF-emitting MMR carrier was prepared to specifically deliver lobeglitazone into plaque macrophages and scaled up for the translational application to the plaques in coronary-sized arteries. Previous studies have reported that D-mannose had higher binding affinity towards mannose receptors than other monosugars (i.e., N-acetylglucosamine, glucose, xylose, and galactose) 33 - 37 . In this study, we used mannosamine as a specific ligand to mannose receptors because it has the equatorial hydroxyl groups at both the C3 and C4 positions that are the principal determinants of recognition towards mannose receptors ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 92%
“…Glycan array screening revealed a fuller picture of the variety of glycans CRD4 is capable of binding. Nearly all the oligosaccharides giving a strong signal included a nonreducing D-mannose or L-fucose moiety (2). The identified D-mannose ligands are all substructures of a Man 9 high-mannose oligosaccharide, and the strongest D-mannose-related signals have terminal D-mannose-alpha-1,2-D-mannose motifs.…”
mentioning
confidence: 94%
“…A solid-phase competition assay allowed the authors to delve more deeply into the glycan interactions. The data showed a Man 9 oligosaccharide binds with 40-fold higher affinity than a D-mannose monosaccharide (2). Testing of disaccharides and trisaccharides suggested that avidity could be responsible for the tighter binding of the branched ligands.…”
mentioning
confidence: 98%
See 2 more Smart Citations